Dalgliesh. Series 3 [videorecording (DVD)] - Edmundson, Helen, 1964- (Acorn, 2025)
Set in 1979, the third instalment of Dalgliesh sees Commander Adam Dalgliesh take on three highly charged and highly sensitive cases. In Death In Holy Orders, he investigates the bloody murder of a senior churchman in a seminary in West Sussex an institution already engulfed in scandal. In Cover Her Face, a murder in the house of a wealthy and influential family brings him to the heart of Essex. Finally, Devices And Desires sees him investigate a string of killings in Kent, suspected of being the work of anti-nuclear campaigners.